Aerosol synthesis of silicon nanoparticles with narrow size distribution—Part 1: Experimental investigations - Körmer, R.; Jank, M.P.M.; Ryssel, H.; Schmid, Hans-Joachim; Peukert, W. (Journal of Aerosol Science)
A study on the feasibility of aerosol processing of nearly monodisperse silicon nanoparticles via pyrolysis of monosilane in a hot wall reactor is presented. For optimal conditions silicon nanoparticles with a geometric standard deviation of 1.06 were synthesized at a production rate of 0.7 g/h. The size of the particles could be precisely controlled in the range of 20–40 nm, whilst maintaining a geometric standard deviation in the range of 1.06–1.08, by proper choice of the governing parameters temperature, residence time and precursor concentration. The results show that narrow particle size distributions can only be obtained in the temperature range between 900 and 1100 °C, as long as both the initial silane concentration (1 mbar silane partial pressure) and the reactor total pressure are low (25 mbar). This regime for the production of narrow particle size distributions has not been identified in prior work on the thermal decomposition of silane. Narrowly distributed particles can be obtained under conditions where nucleation and particle growth are separated and the agglomeration rates are negligible.

Interparticle forces in silica nanoparticle agglomerates - Seipenbusch, M.; Rothenbacher, S.; Kirchhoff, M.; Schmid, Hans-Joachim; Kasper, G.; Weber, A. P. (Journal of Nanoparticle Research)
To improve the understanding of the poor dispersability of fumed silica nanoparticle agglomerates, the stability of highly defined agglomerated model particles was investigated. The high temperature synthesis conditions for fumed silica were simulated by tempering. Along with electron-microscopical analysis of the sintering necks, the interparticle forces were investigated by energy resolved fragmentation analysis based on low pressure impaction. At temperatures above 1,000 °C the fragmentability of the agglomerates rapidly decreased while the energy necessary for fragmentation increased. The development of sintering necks was observed for temperatures exceeding 1,300 °C. Comparison of the experimental data with the fragmentation behaviour of a commercially produced fumed silica indicated solid state contacts (sintering necks) as being most numerous in the agglomerates resulting in limited fragmentability.

Verfahren zur integrierten informationstechnischen Unterstützung des Innovationsmanagements - Ihmels, Stephan

7. Paderborner Workshop Entwurf mechatronischer Systeme - Gausemeier, Jürgen; Rammig, Franz-Josef; Schäfer, Wilhelm; Trächtler, Ansgar

Run-time Reconfigurable Multiprocessors - Purnaprajna, Madhura

Lebensdauerüberwachung in mechatronischen Systemen - Wedman, Sebastian

6. Symposium für Vorausschau und Technologieplanung - Gausemeier, Jürgen

Systematik zur funktionsorientierten Modellierung von Elektrik/ Elektronik-Systemen über den Produktlebenszyklus - Warkentin, Andreas

Adaptable OS services for distributed reconfigurable systems on chip - Samara, Sufyan

On the design and implementation of reliable and economical telematics software architectures for embedded systems : a domain-specific framework - Stehr, Jan